Growth Suppression of Hybrid Bermudagrass with Imazapic - Benjamin D. Pritchard; Devon E. Carroll; Tyler Q. Carr; Gregory K. Breeden; James T. Brosnan (HortScience, 2024)
Imazapic is an acetolactate synthase-inhibiting herbicide labeled for weed control in pastures, rangeland, and noncrop areas. Field research was conducted in Knoxville, TN, USA, during 2020 and 2021 to evaluate the tolerance of four hybrid bermudagrass (Cynodon dactylon × Cynodon transvaalensis Burtt Davy) cultivars to applications of imazapic for growth suppression. Separate experiments were conducted on ‘TifTuf’, ‘Tifway’, ‘Tahoma 31’, and ‘Latitude 36’ hybrid bermudagrass. Experiments included plots (1.5 m2) arranged in a randomized complete block design with four replications and were repeated. Treatments were applied 14 Aug 2020 and 6 Aug 2021, and were mixed with methylated seed oil. Imazapic rates were 0, 35, 52.5, 70, or 105 g⋅ha–1. Cultivar tolerance was assessed via visual ratings of turfgrass injury relative to untreated check plots. Normalized differential vegetation index data were collected on each date turfgrass injury was evaluated. Growth suppression was quantified via reductions in dry clipping weight after mowing. Hybrid bermudagrass injury increased with imazapic rate for all cultivars, and peak injury (> 30%) following all imazapic treatments occurred within 14 days. At the lowest imazapic rate (35 g⋅ha–1), injury was transient, with all hybrid bermudagrass cultivars fully recovered by 28 days. All rates of imazapic reduced hybrid bermudagrass dry clipping weight for 21 days for all cultivars. Further research is warranted to explore lower application rates than those tested in our study, in addition to determining tolerance and growth suppression of other turfgrass species commonly managed on golf courses.